2012
DOI: 10.1007/s00113-011-2102-y
|View full text |Cite
|
Sign up to set email alerts
|

Präklinische Polytraumaversorgung: S3-Leitlinie

Abstract: The guidelines follow the priorities established by the A-B-C-D-E scheme. They focus on the treatment of actual disturbances of vital functions and not so much on their anticipated development. Important recommendations with regard to the indication for intubation and ventilation, fluid therapy, diagnosis and treatment of severe chest injuries (tension pneumothorax in particular), management of severe traumatic brain injury, pelvic and vertebral injuries, priorities in the management of extremity fractures as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…This approach may, however, increase the hydrostatic pressure on the wound, cause dislodgement of blood clots, a dilution of coagulation factors and undesirable cooling of the patient. The concept of low volume fluid resuscitation, so-called "permissive hypotension", avoids the adverse effects of early aggressive resuscitation while maintaining a level of tissue perfusion that, although lower than normal, is adequate for short periods [162]. Its general effectiveness remains to be confirmed in randomised clinical trials; however, two studies published in the 1990s demonstrated increased survival when a low and delayed volume fluid resuscitation concept was used in penetrating [163] or penetrating and blunt [164] trauma.…”
Section: Resultsmentioning
confidence: 99%
“…This approach may, however, increase the hydrostatic pressure on the wound, cause dislodgement of blood clots, a dilution of coagulation factors and undesirable cooling of the patient. The concept of low volume fluid resuscitation, so-called "permissive hypotension", avoids the adverse effects of early aggressive resuscitation while maintaining a level of tissue perfusion that, although lower than normal, is adequate for short periods [162]. Its general effectiveness remains to be confirmed in randomised clinical trials; however, two studies published in the 1990s demonstrated increased survival when a low and delayed volume fluid resuscitation concept was used in penetrating [163] or penetrating and blunt [164] trauma.…”
Section: Resultsmentioning
confidence: 99%
“…On scene, emergency physicians and emergency medical technicians (EMT) can only adequately detect a traumatic PTX by combining single findings of clinical examination [7, 8]. Even if present studies report that a wait-and-see attitude in occult PTX (even in ventilated patients) can be as safe as chest tube placement [14, 15], it is not clear which kind of cases are applicable to this statement [5].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, only mechanism of injury, and clinical examination with assessment of ventilation can be consulted for diagnosing or excluding PTX. Due to low sensitivity (43–90%) and specificity (79–98%) of each single criterion, only their combination allows secure assessment [2, 7, 8]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations